Of sheep, oranges, and yeast : a multispecies impression - Yates, Julian (Posthumanities, 2017)
In what senses do animals, plants, and minerals "write"? How does their "writing" mark our livesour past, present, and future? Addressing such questions with an exhilarating blend of creative flair and theoretical depth, Of Sheep, Oranges, and Yeasttraces how the lives of, yes, sheep, oranges, gold, and yeast mark the stories of those animals we call "human."Bringing together often separate conversations in animal studies, plant studies, ecotheory, and biopolitics, Of Sheep, Oranges, and Yeastcrafts scripts for literary and historical study that embrace the fact that we come into being through our relations to other animal, plant, fungal, microbial, viral, mineral, and chemical actors. The book opens and closes in the company of a Shakespearean character talking through his painful encounter with the skin of a lamb (in the form of parchment). This encounter stages a visceral awareness of what Julian Yates names a "multispecies impression," the way all acts of writing are saturated with the "writing" of other beings. Yates then develops a multimodal reading strategy that traces a series of anthropo-zoo-genetic figures that derive from our comaking with sheep (keyed to the story of biopolitics), oranges (keyed to economy), and yeast (keyed to the notion of foundation or infrastructure). Working with an array of materials (published and archival), across disciplines and historical periods (Classical to postmodern), the book allows sheep, oranges, and yeast to dictate their own chronologies and plot their own stories. What emerges is a methodology that fundamentally alters what it means to read in the twenty-first century